2017
DOI: 10.1111/echo.13768
|View full text |Cite
|
Sign up to set email alerts
|

The impact of volume overload on right heart function in end‐stage renal disease patients on hemodialysis

Abstract: Two-dimensional speckle tracking echocardiography is an easy and noninvasive tool that could provide additional volume-independent echocardiographic parameters and more information on RA physio-mechanics. This might lead to a better evaluation of the cardiac pathophysiology and hemodynamics of patients. Moreover, providing novel volume-independent parameters for the evaluation of right heart chambers would improve the clinical perspectives of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Stated otherwise, a decrease in the LA volume is in tandem with a reduction in the LA conduit function. Concerning the RA, in patients with end-stage renal disease, the RA volume and conduit function decrease after hemodialysis, which is compatible with the aforementioned study regarding the LA (39). It can, therefore, be explained why the inter-study difference vis-a-vis the RA volume index may lead to an inter-study difference in terms of the RA conduit function.…”
Section: The Conduit Functionsupporting
confidence: 85%
“…Stated otherwise, a decrease in the LA volume is in tandem with a reduction in the LA conduit function. Concerning the RA, in patients with end-stage renal disease, the RA volume and conduit function decrease after hemodialysis, which is compatible with the aforementioned study regarding the LA (39). It can, therefore, be explained why the inter-study difference vis-a-vis the RA volume index may lead to an inter-study difference in terms of the RA conduit function.…”
Section: The Conduit Functionsupporting
confidence: 85%
“…Current data support that a mean ultrafiltration rate of >13 mL/kg/h is associated with higher mortality rates in the long term (6-11). The acute effect of rapid ultrafiltration on the cardiac functions has been investigated in some studies (12); however, there is still a lack of data about the exact relationship between acute rapid ultrafiltration and cardiac functions. All previous studies have been limited into studying the impact of HD on peak strain values, and that the potential influence of HD on the temporal characteristics of deformation and especially mechanical dispersion has not been studied until now.…”
Section: Introductionmentioning
confidence: 99%
“…Although strain is considered independent of loading conditions, some studies reported a bettering in strain values ensuing elective HD within minutes or days [ 23 ]. We believe that the amelioration seen in all studied parameters at 6 months after HD initiation is a milestone in the life of an ESKD patient.…”
Section: Discussionmentioning
confidence: 99%